Anti-idiotypic antibodies as cancer vaccines: achievements and future improvements - Ladjemi, Maha Zohra (Frontiers in Oncology, 2012)
Since the discovery of tumor-associated antigens (TAA), researchers have tried to develop immune-based anti-cancer therapies. Thanks to their specificity, monoclonal antibodies (mAbs) offer the major advantage to induce fewer side effects than those caused by non-specific conventional treatments (eg. chemotherapy, radiotherapy). Passive immunotherapy by means of mAbs or cytokines has proved efficacy in oncology and validated the use of immune-based agents as part of anti-cancer treatment options. The next step was to try to induce an active immune protection aiming to boost own’s host immune defense against TAAs. Cancer vaccines are thus developed to specifically induce active immune protection targeting only tumor cells while preserving normal tissues from a non-specific toxicity. But, as most of TAAs are self antigens, an immune tolerance against them exists representing a barrier to effective vaccination against these oncoproteins. One promising approach to break this immune tolerance consists in the use of anti-idiotypic mAbs, so called Ab2, as antigen surrogates. This vaccination strategy allows also immunization against non-proteic antigens (such as carbohydrates). In some clinical studies, anti-idiotypic (anti-Id) cancer vaccines indeed induced efficient humoral and/or cellular immune responses associated with clinical benefit. This review article will focus on recent achievements of anti-Id mAbs use as cancer vaccines in solid tumors.